How do you simplify #(f^-3g^2)/(h^-4)#?

2 Answers
Jul 15, 2018

Answer:

#" "#
#color(red)((f^-3g^2)/(h^-4)=1/(f^3) * h^4*g^2#

Explanation:

#" "#
We are given the expression:

#color(red)((f^-3g^2)/(h^-4)#

Formula used:

#color(blue)(a^(-b)=1/a^b#

#color(blue)(1/(1/a) = a#

Using this formula, we can write

#f^(-3) = 1/f^3#

#h^(-4)=1/h^4#

Hence, we get

#color(red)((f^-3g^2)/(h^-4)=1/(f^3) * h^4*g^2#

Hope it helps.

Jul 15, 2018

nothing cancels down as they are three different variables

But #a^-b=1/a^b# so we can rewrite the expression with no negative powers

#(f^-3g^2)/(h^-4)=(g^2h^4)/f^3#